Corporate insolvencies in times of COVID-19 - Julian Dörr; Georg Licht; Simona Murmann (ZEW - Leibniz Centre for European Economic Research, 2021)
After the outbreak of the COVID-19 crisis, the number of insolvency filings has reached a record low in 2020. However, industry sectors are affected differently. In the early phase of the COVID-19 crisis, the number of insolvencies in the service sector decreased most substantially. In the third quarter of 2020, we observe increasing insolvency numbers throughout all sectors that have, however, not reached pre-crisis level yet. Our analysis shows a pronounced decrease of insolvent micro firms with at most 10 employees until September 2020 while insolvency declarations among micro firms are rising again in the third quarter of 2020. Businesses with fully liable owners avoided insolvency filings to a much greater extent than companies with limited liability. Businesses with owners living abroad are more likely to file for insolvency. The COVID-19 crisis changed the age composition among insolvent entrepreneurs: The number of insolvency filings of older entrepreneurs (above 65 years) has started to catch up with the numbers among young entrepreneurs (below 35 years). In the age groups (35 -50 and 51-65 years) we see a strong decrease in insolvency filings. Insolvency declarations among firms located in Western Germany have dropped more sharply than the numbers in Eastern Germany resulting in a slight increase in the share of Eastern German insolvency filings. We observe no major shifts in the age composition of insolvent firms, the gender composition of insolvent entrepreneurs and entrepreneurial team size.
Keywords: 330; Coronavirus; Wirkungsanalyse; Insolvenz; Wirtschaftskrise; Deutschland